The Predictive Role of Fetal Growth for Placental Invasion Anomalies in Placenta Previa - Koca, Evrim; Dincgez, Burcu; Ozgen, Gulten; Simsek, Deniz (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
To evaluate the predictive role of fetal percentile for placental invasion anomalies in placenta previa cases. Study Design: Retrospective studyPlace & Duration of the Study: Training and Research Hospital, January 2018 and December 2023A total of 298 placenta previa cases was divided into two groups: PAS (placenta accreta spectrum)-positive placenta previa (n=98) and PAS-negative placenta previa (n=200). Then PAS-positive placenta previa cases were divided into two subgroups: placenta increta-accreta (n=59) and placenta percreta (n=39). Sociodemographic findings, obstetric features, fetal percentile measurements between 22 and 28 gestational weeks and perioperative characteristics of patients were recorded and compared between groups.Fetal percentile was significantly lower in PAS-positive placenta previa cases as compared to PAS-negative placenta previa cases (p<0.001). Moreover, fetal percentile≤52.5 discriminated PAS-positive placenta previa cases from PAS-negative placenta previa cases with 75.51% sensitivity and 51.5% specificity (p<0.001, AUC=0.654). In multivariate analysis, a fetal percentile of 52.5 and below increased the risk of PAS by approximately 4 times (Hosmer–Lemeshow p=0.101, model p<0.001). No significant difference was detected between placenta percreta and placenta accreta-increta groups in terms of fetal percentile (p=0.224). Fetal percentiles calculated between 22 and 28 gestational weeks could discriminate PAS-positive placenta previa cases from PAS-negative placenta previa cases, although it had no role in discriminating placenta percreta from accreta and increta cases. Therefore, the evaluation of fetal percentile in placenta previa cases can be considered as a supportive finding in the prediction of invasion anomaly although it does not determine the depth of invasion.
Keywords: accreta; fetal percentile; increta; percreta; placental invasion